EXPLORING TECHNOLOGY DECEPTION PERCEPTIONS IN THE INDIAN BANKING SECTOR - MAHABOOB, MOHAMMAD; SATTI BABU, K. (International Journal of Psychosocial Rehabilitation, 2019)
In order to survive and expand in the financial industry, the banking climate of today is extremely competitive and constantly changing. Modern technology is a "enabling resource" that can support the development of more adaptable and flexible learning structures. Additionally beneficial is the bank’s ability to swiftly adopt the market condition. The primary goal of this study was to analyze how customers perceive technological deception in banks. The findings show that the three main dimensions of customer deception perception are Information Securities Factors (IS), Preventive Measures (PM), and New Online Services (NOS). In summary, bankers ought to advise clients on safe online transactions, work with them to prevent technological fraud in banks, and emphasize that clients should protect their personal information and only use secure Wi-Fi when conducting online banking transactions.